Enhancing Community Cooperation through Network Governance and Smart Specialisation to Mitigate Social Conflicts - Korchynska, Oleksandra; Levytska, Yana; Chumakova, Hanna; Ahieieva, Iryna; Leskiv, Taras; Корчинська, Олександра Остапівна; Левицька, Яна Вікторівна; Чумакова, Ганна Володимирівна; Агєєва, Ірина Вікторівна; Леськів, Тарас Сергійович (Great Britain : Modestum Publishing, 2025)
EN: Introduction: The relevance of the research topic is primarily in introducing the concepts of network management and smart specialisation to strengthen social ties, avoid social conflicts and increase the competitiveness of communities through interactive information exchange and active participation of stakeholders. Objectives: The main aim of writing a scientific article is to substantiate the need to apply network management practices and smart specialisation within the framework of community cooperation to prevent social conflicts. Methods: During the study, several general scientific methods of cognition were used, including induction, synergy, comparative analysis, deductive and analytical methods, and systematisation and generalisation. Results: The study identified areas for effectively implementing network management principles in Ukraine, including developing a unified methodology for evaluating results, a long term register of initiatives and partnership mechanisms, strengthening territorial communities, adapting the project approach, and increasing its maturity. In addition, priority areas for improving the current strategy of smart specialisation of Ukraine's regions and ways to optimise community cooperation have been identified, including introducing a data collection system, coordinating participants, integrating technologies, and developing communication strategies. Conclusions: Thus, the developed measures to optimise community cooperation, based on network management and smart specialisation of regions, allow for meeting society's current needs and strengthening the community population's trust in state institutions, ensuring their effectiveness and sustainable development of the region of Ukraine.
Підвищення ефективності співпраці територіальних громад шляхом мережевого врядування та смарт-спеціалізації з метою зниження соціальних конфліктів
Keywords: network management; smart specialisation; public administration; cooperation; decentralisation; development strategy; social conflict; society; region; community; мережеве управління; смарт-спеціалізація; публічне управління; співпраця; децентралізація; стратегія розвитку; соціальний конфлікт; суспільство; регіон; громада